COMPARACION CITOGENETICA DE DOS POBLACIONES DE Aedes aegypti en Colombia - Bello García, Felio J.; Departamento de Biología Facultad de Ciencias Pontificia Universidad Javeriana, Bogotá (2013)
Two populations of Aedes a.egypti from Sahagun (Cordoba) and Anapoima were compared onthe basis oftheir cytogenetic characteristics and their protein phenotypes. The diploid chromosome number for the species 2n = 6 was confirmed. There were no significant differences for the .&tandard measurements ofthe chromosomes in the air-dried when using squash techniques, they showed significant differences for the chromosome length. However, the relative length and the absolute average lengths were similar in the two populations with both procedures. These data support the. idea that these types of values reduce the effects of technicaf manipulations. G and R banding showed similar patterns for the karyotypes of the two populations, and the Cbands confirmed the position ofthe centromere. The three chromosome paii-s are metacentric, and the X chromosome showeda · · cleár and distinct heterochromatic band in the q arm as a sex marker which is absent in the Y chromosome. Electrophoretic patterns of soluble proteins showed the same number ofbands for.both populations of Aedes aegyptibut the average content of protein per band was different. This m ay suggest adaptative responses to the environmental differences in the two geographical pl1:1.ces.